Michel Foucault versus Kritisi Kaum Feminist - Konrad Kebung (Litbang STFT Widya Sasana Malang, 2021)
The paper presents Foucault's rich philosophical thoughts and analyses on various fields in the historical and cultural settings, and how his ideas are critiqued by feminists of various movements. Although his analyses are really productive and helpful for many feminists in pursuing their studies and activities, yet there are also many critics coming from the feminist group that Foucault's analyses are so androcentrism, namely centralized too much on man (patria potestas), as if woman is identical with man physically and psychologically. Foucault therefore is seen as